Analysis of an algorithm incorporating limited and whole-leg assessment of the deep venous system in symptomatic outpatients with suspected deep-vein thrombosis (PALLADIO): a prospective, multicentre, cohort study. Issue 11 (November 2015) - Ageno, Walter; Camporese, Giuseppe; Riva, Nicoletta; Iotti, Matteo; Bucherini, Eugenio; Righini, Marc; Kamphuisen, Pieter W; Verhamme, Peter; Douketis, James D; Tonello, Chiara; Prandoni, Paolo; ,
Summary: Background: Compression ultrasonography is the mainstay of diagnosis of deep-vein thrombosis (DVT) of the legs. Compression ultrasonography can be extended to the entire deep venous system (whole-leg) or restricted to the proximal veins only (limited), and the two approaches are clinically equivalent. We aimed to assess the diagnostic value of an algorithm combining whole-leg and limited compression ultrasonography. Methods: We did a prospective, multicentre, cohort study at eight centres in five countries. Consecutive outpatients aged 18 years or older with suspected DVT underwent D-dimer measurement and pretest clinical probability assessment. DVT was ruled out without further testing if pretest probability was unlikely and D-dimer was negative (group 1). Patients in whom either pretest probability was likely or who were positive for D-dimer underwent limited compression ultrasonography only (group 2). Finally, patients in whom pretest probability was likely and who had a positive measurement for D-dimer underwent extended whole-leg compression ultrasonography (group 3). All patients in whom DVT was ruled out were followed up for 3 months. The primary outcome was the incidence of objectively recorded venous thromboembolism. The primary analysis included all patients managed according to the study protocol. This study is registered withClinicalTrials.gov, numberNCT01412242 . The final results are reported here. Findings: Between March 1, 2011, and July 31, 2014, 1348 consecutive outpatients were referred for this study, of whom 1162 were eligible to participate. After pretest probability assessment and D-dimer testing, 351 were in group 1, 401 in group 2, and 410 in group 3. Limited compression ultrasonography was positive in 12 (3%) patients in group 2 and extended whole-leg compression ultrasonography was positive in 200 (49%) patients in group 3. 82 (39%) of all DVT diagnosed at baseline were isolated distal thromboses. 26 protocol violations were reported. Thus, 351 patients from group 1, 371 patients in group 2, and 202 patients in group 3 who had been excluded for DVT by the algorithm were included in the primary analysis at 3 months. One, four, and three DVTs were reported, respectively. Thus, the 3-month incidence of venous thromboembolism in untreated patients after a negative diagnostic strategy was 0·87% (95% CI 0·44–1·70). Interpretation: An algorithm combining limited and whole-leg compression ultrasonography could be a reliable, safe, and convenient method for diagnostic management of outpatients with clinically suspected DVT. Funding: None.